Teaching Western American literature - Harrison, Brady, 1963-; Tanglen, Randi Lynn (Postwestern horizons., 2020)
"'Teaching Western American Literature' gives instructors a glimpse into the classrooms, syllabi, and assignments of leading scholars in the field"--